ANALYZING DIGITAL MARKETING, GREEN MARKETING, NETWORKING AND PRODUCT INNOVATION ON SUSTAINABILITY BUSINESS PERFORMANCE, SILK CLUSTER IN POLEWALI-MANDAR, WEST SULAWESI - Erwin, Erwin; Suade, Yuyun Karystin Meilisa; Poernomo, Winarto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to find out the influence of Digital Marketing, Green Marketing, Networking and Product Innovation on the Sustainability Business Performance of the Silk Cluster in Polewali Mandar, West Sulawesi. With the number of respondents as many as 30 silk business people, both weaving and just steaming the woven products. The instrument in the questionnaire is measured using a Likert scale (5 scales), while the variables are 1) Independent Variables consisting of Digital Marketing, Green Marketing, Networking, Product Innovation, 2) Dependent Variable is Sustainability Business Performance. The analysis used in this study is the Partial Least Square Structural Equation Model (PLS SEM). The results show that only Product Innovation has a positive and significant effect on Sustainability Business Performance (β= 0.328; =0.022), while Digital Marketing has a positive but not significant effect (β= 0.025; =0.445), for Networking it has a positive effect. Negative but not significant (β= -0.030; =0.434) and Green Marketing actually has a negative and significant effect on Sustainability Business Performance (β= -0.277; =0.046). Keywords: Digital Marketing, Green Marketing, Networking, Product Innovation, Sustainability Business Performance